Relationship between emotional elder abuse and developmental function of the family - Monireh Amirmohammadi; Nasrin Nikpeyma; Reza Negarandeh; Shima Haghani; Zahra Amrollah Majdabadi (Wiley, 2023)
Abstract Aim This study aimed to assess the relationship between emotional elder abuse and the developmental function of the family. Design Community‐based correlational cross‐sectional study was conducted. Methods Data were collected on 265 older adults from July to October 2019 in Tehran‐Iran. The samples were selected by simple random sampling and they completed self‐report tools: demographic information, emotional elder abuse developmental function in the family. Data analysis was performed using descriptive and inferential statistics and SPSS software v.16. Results Mean score of the developmental function in the family was 67.38 (SD = 3.22, range = 0-129). There was a significant negative correlation between the total score of developmental function in the families and emotional elder abuse. Moreover, there was a relationship between the subscale of care and regulation, being attracted to human relationships, purposeful exchange, and creating representatives and ideas with emotional elder abuse.